The Cooperation Form of SMK Karya Teknologi Jatilawang of Technology and Industry Group with Astro Parts in the Framework of Forming an Entrepreneurial Spirit - Widyatama, Monelis; Khumaedi, Muhammad; Widjanarko, Dwi (Universitas Negeri Semarang, 2018)
The cooperation form of SMK KaryaTeknologi Jatilawang of technology and industry group with Astro Partss in the framework of forming an entrepreneurial spirit. This research aims to describe and analysis (1) the cooperation form of SMK KaryaTeknologiJatilawang with Astro Partss, in terms of forming the entrepreneurial spirit in students; (2) which form of cooperation is the most dominant in the formation of entrepreneurial spirit in students. The cooperation of SMK KaryaTeknologiJatilawang with Astro Partss aims to develop studentsâ€™ soft skills and competency ability in order to be ready and able to face the world of work. The research be used is a design qualitative research. The research approach is meant to learn deeply by examines, analyses, and describes based on data in SMK KaryaTeknologiJatilawang. The data collection technique which used are observation, interview and documentation which are continued with data source triangulation method to check data validity. The result of this research is SMK KaryaTeknologiJatilawang gets the cooperation form with Astro Partss, the forms are; (1) foster father â€“Â foster child; and (2) dual system; and (3) industrial culture ; (4) training; and (5) agency. The last result of this research can be known the cooperation form of agency is the most dominant cooperation form in terms of forming the entrepreneurial spirit in students.